2018
DOI: 10.20944/preprints201810.0160.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety Evaluation of Absorbent Hygiene Pads: a Review on Assessment Framework and Test Methods

Abstract: Disposable absorbent hygiene products have evolved for superior performance, enhancing the convenience of daily lives. Yet the use of disposable hygiene pads has brought safety concerns on chemical exposure, and significant efforts have been made to assess the potential risks associated with use of hygiene pads. This article intends to overview the safety assessment framework of diapers and feminine pads, which includes hazard identification, hazard characterization, exposure assessment, risk characterization,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…Pads are being treated with carcinogenic bleaching agents like dioxin to give a whitish and healthier appearance the impact of which is under research. 17 On an average woman use 10000 to 11000 pads throughout her life and gets exposed to them every month. The silver lining for avoiding stains increases the risk of bacterial and fungal infections and the absorbent gel from petroleum polymers can induce allergies and harbor infections.…”
Section: Health and Environmental Impactmentioning
confidence: 99%
“…Pads are being treated with carcinogenic bleaching agents like dioxin to give a whitish and healthier appearance the impact of which is under research. 17 On an average woman use 10000 to 11000 pads throughout her life and gets exposed to them every month. The silver lining for avoiding stains increases the risk of bacterial and fungal infections and the absorbent gel from petroleum polymers can induce allergies and harbor infections.…”
Section: Health and Environmental Impactmentioning
confidence: 99%
“…This study estimated adult nappy waste with the average values reported by the ICS for urinary incontinence, 35% for women, and 17.5% for men, both aged above 65 years. Also, it was assumed that each adult uses an average of four nappies per day, and that one used nappy weighs 320 g (Bae et al, 2018; Knowaste, 2019a; Rai et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…For countries where data were unavailable, it was supposed that 50% of women use sanitary pads. Finally, it was presumed that each woman used an average of six pads per day during seven days of a month, and each used pad weighs 35 g (Bae et al, 2018; Elledge et al, 2018; Woeller and Hochwalt, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory classifications of feminine hygiene pads vary among countries and are regulated by different administrative organizations in each country. For example, in the United States, the Food and Drug Administration is in charge of regulation of sanitary pads; in EU, pads are regarded as 'broadly applicable consumer products'; and, in South Korea, they are regulated under the guidelines of 'quasi-grugs' [60]. Regulatory organizations such as the European Chemicals Agency, scientific committees like the National Academy of Sciences, and authoritative institutions such as the World Health Organiza-tion proclaim a systematic risk assessment protocol to examine chemical safety in these products.…”
Section: Regulatory Risk Assessment Of Sanitary Padsmentioning
confidence: 99%